Similar strength gains at lower perceived efforts via cluster set vs. traditional home-based online training: A 6 weeks randomized controlled trial - Rappelt, Ludwig; Held, Steffen; Leicht, Mario; Wicker, Pamela; Donath, Lars (Frontiers in Sports and Active Living, 2022)
Cluster Training (CT) has been shown to induce strength at lower perceived efforts compared to traditional training (TRT) with sets performed to repetition failure. These findings have not yet been extended to remote online training in middle-aged to older people. Thus the present study aimed at investigating whether a cluster set online training with bodyweight exercises is similar in its effectiveness a more demanding traditional strength training employed with a traditional set structure. A total of n = 21 participants (14 female, 55 ± 12 years, 76.4 ± 16.1 kg, 1.71 ± 0.10 m, 74 ± 72 min of activity/w) were randomly assigned to either a CT or volume-, load-, and work-to-rest-ratio-matched TRT. After an initial 6-week run-in-phase, all participants were engaged into an online live-instructed full-body workout twice a week (40 min each) for a period of 6 weeks. Rates of perceived efforts (RPE) were assessed for each session (session RPE; sRPE). Changes in maximal voluntary contraction (MVC) at leg press (LP) and abdominal press (AP) as well as one-minute-sit-to-stand and Y-Balance-Test (YBT) were compared between BASELINE and PRE (ΔRUN-IN) and between PRE and POST (ΔINTERVENTION). In LP, TRT showed greater improvements with large effect sizes in ΔINTERVENTION compared to ΔRUN-IN. In CT, greater improvements with moderate effects were found in ΔINTERVENTION compared to ΔRUN-IN. In AP, both CT and TRT showed larger improvements with large effect sizes in ΔINTERVENTION compared to ΔRUN-IN. In YBT, a significant and large main effect for time was found indicating larger improvements for ΔINTERVENTION compared to ΔRUN-IN. CT showed lower sRPE than TRT. Both CT and TRT led to similar adaptations in MVC and balance performance. However, the perceived effort of CT was rated lower than for TRT. Therefore, conducting resistance training with a cluster set structure seems to be a suitable approach for training programs in middle-aged and older people.